2018
DOI: 10.1186/s12889-018-6179-x
|View full text |Cite
|
Sign up to set email alerts
|

Do sex differences in reported weight loss intentions and behaviours persist across demographic characteristics and weight status in youth? A systematic review

Abstract: BackgroundEvidence suggests that young females are more likely to try to lose weight than young males, however whether this sex difference persists across demographic characteristics and weight status is unclear. Further, whether females are more likely than males to try to lose weight using unhealthy weight loss strategies has never been systematically assessed. The objective of this systematic review was to examine the literature on sex differences in weight loss intentions and strategies in children and ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 67 publications
(237 reference statements)
0
6
0
Order By: Relevance
“…Male adults not only lose weight faster but tend to lose more weight than their female counterparts [78][79][80][81][82]. These differences may be explained by distinct motivations, individual preferences, and cultural norms to engage in specific health behaviors such as PA [83] or dieting [84], which are evident among youth. In one study, female adolescents reported less PA and engaged in shorter durations of activity than male adolescents [85], with a higher exercise dose potentially resulting in greater weight loss [86].…”
Section: Discussionmentioning
confidence: 99%
“…Male adults not only lose weight faster but tend to lose more weight than their female counterparts [78][79][80][81][82]. These differences may be explained by distinct motivations, individual preferences, and cultural norms to engage in specific health behaviors such as PA [83] or dieting [84], which are evident among youth. In one study, female adolescents reported less PA and engaged in shorter durations of activity than male adolescents [85], with a higher exercise dose potentially resulting in greater weight loss [86].…”
Section: Discussionmentioning
confidence: 99%
“…In the present sample, female students were more likely than male students to engage in all types of weight control behaviors, which in consistent with previous reports. 41 , 42 This result may be attributed to the fact that women are more likely to experience weight stigma and face greater pressure to conform to the thin ideal. 40 However, men should not be overlooked in eating disorder research, as eating disorders and unhealthy weight loss practices among men are likely underdiagnosed, despite the fact that their prevalence continues to rise.…”
Section: Discussionmentioning
confidence: 99%
“…40 Notably, similar proportions of both sexes use various weight loss strategies, with diet and exercise being the most prevalent among both women and men. 41 , 42 However, weight loss behaviors remain understudied in men. 41 …”
Section: Introductionmentioning
confidence: 99%
“…Our findings of the relationships between weight loss attempts and sociodemographic characteristics are generally consistent with those previously reported. For example, it has been reported that the prevalence of self-reported dieting is higher in older children14 16 and girls12 17 18 compared with younger children or boys. Although we found the absolute prevalence was constantly higher among girls, we found a significant increase in weight loss attempts over time among boys from both age groups but not in girls.…”
Section: Discussionmentioning
confidence: 99%